Optimization of the Building Envelope and Roof Shading to Reduce the Energy Consumption of College Low-Rise Buildings in Indonesia - Nasruddin, Nasruddin; Alam, Azimil Gani; Sohel, Mohammad Imroz (UI Scholars Hub, 2023)
Energy consumption in buildings is a crucial concern globally, prompting researchers to explore innovative solutions to mitigate its impact. This study investigates the optimization of building envelopes and roof shading systems of existing buildings in Indonesia to realize notable energy savings. Multiple scenarios were explored, with modifications to building envelopes and roof shading, highlighting the overall thermal transfer value as a key parameter. Using EnergyPlus simulations, the efficacy of natural ventilation in corridors and roof shading modifications was assessed in reducing energy consumption. The findings revealed that renovating existing buildings by optimization of the building envelope and roof shading by simulations can contribute considerably to energy conservation. Various scenarios produced distinct energy savings, underscoring the importance of empirically planned modifications. Substantial reductions in energy and even water consumption were realized by applying natural ventilation in corridors and modifying roof shading, demonstrating a promising approach. Furthermore, avenues for future research were discussed, pointing toward the need for comprehensive analyses of diverse building types, climates, and geographical locations. This study can serve as foundational step toward developing practical guidelines for energy-saving retrofits in existing buildings in Indonesia and similar climate.